Pengaruh Besaran Initial Return terhadap Performa Jangka Panjang Saham Perusahaan - Gavin Adrian; Michael Adityakrisna Rahardja; Aulia Nurul Huda (Studi Akuntansi dan Keuangan Indonesia, 2019)
This research attempts to find relationship between initial return when IPOs with long term performance of company’s stock with buy and hold return as the indicator at Indonesian Stock Exchange. Previous researches argue that positive initial return occurs due to market overreaction and companies taking windows of opportunity and this is also the cause of poor long-term performance. Using cross-sectional regression method, this research finds a significant negative relationship between initial return with three years buy and hold return. This finding is in line with previous researches in various markets that state market overreaction as a cause of positive initial return and therefore the price shaped on the first trading day is too high. This “wrong” price would be adjusted as time goes on. This research also finds that it needs 3 years for the price to be corrected, indicated by the non-significant coefficient of initial return when being regressed to buy and hold return for 1 year and 2 years.